Finessing the Demonology of War: Toward a Practical Aesthetic of Humanising Dissent - Ivie, Robert L. (Javnost-The Public, 2007)
This essay examines peace-building communication in an adversarial world by pursuing an unlikely comparison between the crisis-managing discourse of President Kennedy and Chairman Khrushchev in 1962 and the prophetic Christian voice of Jim Wallis’ antiwar dissent since 9/11. It draws from these cases the rudimentary form of a humanising aesthetic, in which political actors – whether resisting the demonology of war as decision makers or dissenters – devise the discursive equivalent of a stereoscopic gaze out of the language of position and vision. This rhetorical exercise in reflexive perspective taking facilitates the perception of a strategic interdependency between antagonists, confounds the projection of evil, and circumvents rituals of redemptive violence.